Grass Carp (Ctenopharyngodon idella) KAT8 Inhibits IFN 1 Response Through Acetylating IRF3/IRF7 - Li, Meifeng; Hu, Jihuan; Mao, Huiling; Li, Dongming; Jiang, Zeyin; Sun, Zhichao; Yu, Tingting; Hu, Chengyu; Xu, Xiaowen (Frontiers in Immunology, 2022)
Post-translational modifications (PTMs), such as phosphorylation and ubiquitination, etc., have been reported to modulate the activities of IRF3 and IRF7. In this study, we found an acetyltransferase KAT8 in grass carp (CiKAT8, MW286472) that acetylated IRF3/IRF7 and then resulted in inhibition of IFN 1 response. CiKAT8 expression was up-regulated in the cells under poly I:C, B-DNA or Z-DNA stimulation as well as GCRV or SVCV infection. The acetyltransferase domain (MYST domain) of KAT8 promoted the acetylation of IRF3 and IRF7 through the direct interaction with them. So, the domain is essential for KAT8 function. Expectedly, KAT8 without MYST domain (KAT8-△264-487) was granularly aggregated in the nucleus and failed to down-regulate IFN 1 expression. Subcellular localization analysis showed that KAT8 protein was evenly distributed in the nucleus. In addition, we found that KAT8 inhibited the recruitment of IRF3 and IRF7 to ISRE response element. Taken together, our findings revealed that grass carp KAT8 blocked the activities of IRF3 and IRF7 by acetylating them, resulting in a low affinity interaction of ISRE response element with IRF3 and IRF7, and then inhibiting nucleic acids-induced innate immune response.